Impact of Exogenous Application of Indole-3-Acetic Acid on Growth, Yield and Nutritional Quality of Tomato (Journal of Science and Technology Research, 2026)
Four distinct dosages of indole-3-acetic acid (IAA) were used in a single-factor experiment to examine the effects of exogenous IAA administration on tomato growth, yield, and quality. The dosages of IAA were as follows: (i) Control (no IAA), (ii) 50 ppm IAA, (iii) 100 ppm IAA, and (iv) 150 ppm of IAA. Three replications of the experiment were set up using a randomized complete block design. The BARI Tomato-15 had was utilized as the test material. Fruit yield and growth, as well as its nutritional value were significantly impacted by IAA. The 150 ppm of IAA treatment generated the tallest plant (85.49 cm), the maximum number of leaves (26.00), the minimum number of days (29.34 days) needed for the first flowering, the maximum number of flower clusters per plant (15.17), the number of flowers per plant (37.50), and the number of fruits per plant (32.17). The fruit length, weight and yield (96.44 t/ha) were the highest in 100 ppm of IAA. 86.29% (96.44 t/ha) more yield was obtained when treated with 100 ppm of IAA than control (51.77 t/ha). On the other hand, 12.98% (45.05 t/ha) yield reduction occurred in BARI Tomato-15 when treated with 150 ppm of IAA as compared to control (51.77 t/ha). Results revealed that 29.03% TSS, 35.71% TA of fruit increased in 150 ppm of IAA than control and 8.16% pH value decreased in 150 ppm of IAA than control.J. of Sci. and Tech. Res. 6(2): 15-21, 2025